Fast-track development of vaccines for SARS-CoV-2: The shots that saved the world - Vivek P. Chavda; Qian Yao; Lalitkumar K. Vora; Vasso Apostolopoulos; Chirag Patel; Rajashri Bezbaruah; Aayushi Patel; Zhe‐Sheng Chen (2022)
In December 2019, an outbreak emerged of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) which leads to coronavirus disease 2019 (COVID-19). The World Health Organisation announced the outbreak a global health emergency on 30 January 2020 and by 11 March 2020 it was declared a pandemic. The spread and severity of the outbreak took a heavy toll and overburdening of the global health system, particularly since there were no available drugs against SARS-CoV-2. With an immediate worldwide effort, communication, and sharing of data, large amounts of funding, researchers and pharmaceutical companies immediately fast-tracked vaccine development in order to prevent severe disease, hospitalizations and death. A number of vaccines were quickly approved for emergency use, and worldwide vaccination rollouts were immediately put in place. However, due to several individuals being hesitant to vaccinations and many poorer countries not having access to vaccines, multiple SARS-CoV-2 variants quickly emerged that were distinct from the original variant. Uncertainties related to the effectiveness of the various vaccines against the new variants as well as vaccine specific-side effects have remained a concern. Despite these uncertainties, fast-track vaccine approval, manufacturing at large scale, and the effective distribution of COVID-19 vaccines remain the topmost priorities around the world. Unprecedented efforts made by vaccine developers/researchers as well as healthcare staff, played a major role in distributing vaccine shots that provided protection and/or reduced disease severity, and deaths, even with the delta and omicron variants. Fortunately, even for those who become infected, vaccination appears to protect against major disease, hospitalisation, and fatality from COVID-19. Herein, we analyse ongoing vaccination studies and vaccine platforms that have saved many deaths from the pandemic.